Health beliefs and health seeking behaviors of army soldiers with tuberculosis - Tayawa-Villalba, Miriam
TUBERCULOSIS (TB) is a problem of global importance and considered the world's leading infectious killer. Eight million people develop the active disease and two million people die from this disease annually. In the Philippines, TB remains a major public health and socio-economic problem. It persists as one of the leading infectious but preventable diseases that have serious and debilitating effects on individuals, families and communities. It entails looking into the socio-economic, behavioral and cultural factors that affect the problem. It likewise requires understanding of the dynamics of the many facts of the problem at the individual, community and structural levels.
In view of the above findings, the study recommends that an instructional package can be developed and integrated on Retraining Program for soldiers, in Troop & information Education (TI&E) and Physical Examination for Soldiers; an intensive coordination be made by the Office of Army Surgeon to Department of Health (DOH) for creation of DOTS Center in the Philippine Army; a comprehensive program on TB which includes active case findings and complete treatment of confirmed cases be formulated; a review of policies on profiling system of military personnel be conducted, and finally, inclusion of TB module to TI & E and Retraining Programs. Modules be made compulsory.
Thesis (M.A. Nursing)--University of the Philippines Manila.
Keywords: Tuberculosis -- Philippines. -- Research; Tuberculosis -- Philippines. -- Armed Forces -- Research